Effective family engagement policies a guide for early childhood administrators. - McKay, Teresa S. (London : Routledge, 2022)
Aligned with the National Association for the Education of Young Children's Principles of Effective Family Engagement, this book helps early childhood administrators create effective family engagement policies that work. For each of the six key principles, this accessible guide walks leaders through the process of creating effective policy to engage families in their program. Filled with workable documents and templates to thoroughly scaffold the entire process, administrators will finish the work ready to implement the policies created, or build a plan tailored to their specific program. Designed for schools discouraged by the lack of engagement with all families, this book helps leaders strengthen the bondamong home, school, and community.
Keywords: Early childhood education -- Parent participation; Early childhood education -- Management; EDUCATION / Preschool & Kindergarten; EDUCATION / Parent Participation